Creation of a three-dimensional point cloud model of the residential complex "Ozera Jozefa" - Valkova, V.; Shylo, Yevhenii (My University, 2023)
Geodetic works were carried out at the address Hordynskykh 15а Street, in the city of Lviv. The residential complex "Ozera Jozefa" is an upscale, club-type building situated in a cozy green corner of Lviv, near the Piskovi Ozera Park. The building has 6 floors and an underground parking facility, accommodating only 20 apartments. The construction technology is based on monolithic-frame construction. The building is equipped with a modern ventilated facade system, the main advantage of which is the free circulation of air between the facing and the wall. This allows for the efficient removal of moisture and condensation from the facade structure. Additional insulation is provided by a layer of mineral wool. This system helps to retain heat in the rooms during winter and prevent wall overheating in the summer. Additionally, it offers high sound insulation. To develop the facade, windows, and door openings, it is necessary to create a point cloud 3D model of the structure.
Keywords: житловий комплекс «Ozera Jozefa»; м. Львів; геодезичні роботи; тривімірна модель хмари точок; residential complex "Ozera Jozefa"; Lviv; geodetic works; 3D point cloud model